EMPLOYEES' GOAL ORIENTATIONS, THE QUALITY OF LEADER-MEMBER EXCHANGE, AND THE OUTCOMES OF JOB PERFORMANCE AND JOB SATISFACTION. - Janssen, O.; Van Yperen, N. W. (Academy of Management Journal, 2004)
As hypothesized, data from 170 employees of a Dutch firm showed that the quality of leader-member exchange mediated positive relationships between a mastery orientation and leader-rated in-role job performance, leader-rated innovative job performance, and job satisfaction. In contrast, a performance orientation was negatively related or unrelated to those outcomes. These findings suggest that employees with stronger mastery orientations are more effective on the job because they tend to establish higher-quality exchanges with their supervisors.